Perbedaan Metode Rangkaian Bermain dan Metode Rangkaian Latihan terhadap Keterampilan Menggiring Bola - M. Taheri Akhbar (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2019)
This study aims to determine the differences between the play circuit method and the training circuit method for student dribbling skills. This type of research is experimental research. The population in this study amounted to 44 players. The sample in this study overall from a population of 44 people. Data collection techniques with tests. Data analysis techniques using the F Test and Tuckey Test. The Tuckey Test Analysis Results obtained the mean score of the group training method = 40.81 significantly higher than the mean score of the training method of group training exercises = 39.21 (Qh = 3.14> Qt = 2.93). Results of data analysis obtained Fcount = 4.94 while Ftable = 4.06. Based on the analysis of the data it can be concluded that the value of Fcount = 4.94> Ftable = 4.06 thus it can be concluded that there are differences between the play circuit method and the training circuit method on dribbling skills. Keywords: Method of Playing Series, Training Series, Dribbling Skills.